Who is behind the stocking of energy-dense foods and beverages in small stores? The importance of food and beverage distributors. Issue 18 (3rd October 2017) - Ayala, Guadalupe X; D'Angelo, Heather; Gittelsohn, Joel; Horton, Lucy; Ribisl, Kurt; Sindberg, Lesley Schmidt; Olson, Christina; Kharmats, Anna; Laska, Melissa N
Abstract: Objective: The present study examined food and beverage distributors' sourcing, placement and promotion of obesogenic (energy-dense, nutrient-poor) product categories from the perspective of small food store owners/managers. The obesogenic product categories of interest were savoury snacks, sugary beverages, sweet snacks, confectionery and frozen treats. Specifically, we examined how frequently distributors sourced these products, and the types of agreements and expectations they had for their placement and promotion. Differences were explored by store size and ethnicity. Fresh produce was used as a comparison when examining differences in frequency of sourcing only, with implications for healthy food access. Design: Survey research involving in-person interviews. Setting: Four urban areas in the USA: Baltimore, MD; Durham, NC; Minneapolis/St. Paul, MN; and San Diego, CA. Subjects: Seventy-two small food store owners/managers, 65 % consent rate. Results: Most distributors sourced obesogenic products weekly. Agreements to place products were predominantly informal (e.g. handshake) with sweet snack, confectionery and frozen treat distributors, and formal (e.g. contract) with savoury snack and sugary beverage distributors. Free-standing displays were the most common incentive provided by distributors and they expected some control over their placement and pricing. Free/discounted products and signage were also common incentives but slotting fees were not. Smaller stores and ethnic stores were less likely to receive various incentives, but among sweet snack distributors, they were more likely to control the price in ethnic v . non-ethnic stores. Conclusions: Obesogenic products are ubiquitous. Influencing what is made available to consumers in the retail food environment needs to consider the distributor.